CORRELATION OF TESTS FOR EVALUATING EXPLOSIVE STRENGTH AND AGILITY OF FOOTBALL PLAYERS - Alen Kapidžić; Melika Muratović; Haris Pojskić; Jasmin Bilalić; Edin Užičanin (Sport Scientific And Practical Aspects, 2025)
The primary purpose of this research is to determine correlation of variables for evaluating explosive strength and agility, as well as variables for evaluating situational effectiveness of football players. For the needs of this research, two tests for evaluating agility were designed. In each test there are six changes of movement direction, three changes to the left and three to the right side, with the difference between the two designed tests in the distance covered between two changes of direction. The research was conducted on the sample of 52 (fifty-two) examinees, which included freshman (first-year) and sophomore (second-year) students of Faculty for physical education and sport, University of Tuzla. All examinees are active football players in lower levels of competition, therefore they can be classified to the group of amateur football players. The age of examinees chosen for this research was in the range of 19±3, the average height was in the range of 187±17 cm, while the average weight was 77±18 kg. Cronbach's alpha was calculated for the tests which were designed for the needs of this research to determine reliability of tests. Cross-correlation analysis was used to determine correlation between the used variables. Results of the research show that variables for evaluating explosive strength were more dominant for changes of direction where the distance covered between two changes is smaller. Also, it can be seen that variables 20M and DJ have higher correlation coefficients with change of direction tests (SRED3-90, SRED7-90), which means that due to lengthening and shortening cycle, reactive strength is important for implementation of all above mentioned tests. Variables for evaluating explosive strength did not achieve any statistically significant correlations with variables for evaluating situational effectiveness of football players, and one of the reasons for this is insufficient tactical preparation.